2019
DOI: 10.1002/clc.23268
|View full text |Cite
|
Sign up to set email alerts
|

GDMT for heart failure and the clinician's conundrum

Abstract: Therapeutic advances in management of CHF have decreased mortality and have impacted progression in patients with mild to moderate heart failure. Aggressive campaigns by cardiology societies aimed at increasing implementation of these measures in routine practices have almost generalized the treatment of heart failure irrespective of individual variations of clinical status of patients and stages of heart failure. This explains why morbidity compression and quality of life improvement have not been realized fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 60 publications
(71 reference statements)
0
9
0
Order By: Relevance
“…In the present study, the proportion of patients on triple therapy (three evidence‐based HF therapies) remained less than 20% and use of ARNI and SGLT2i remained less than 2%. Various patient‐level (affordability, willingness to take multidrug regimens), clinician‐level (comfort with newer agents, knowledge gaps, treatment inertia), and health system‐level (local treatment availability, access to healthcare) issues may contribute to observed gaps in evidence‐based therapies 19,21,22,24 . Multilevel quality improvement initiatives are needed to promote equitable and widespread care practices to optimize GDMT.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the proportion of patients on triple therapy (three evidence‐based HF therapies) remained less than 20% and use of ARNI and SGLT2i remained less than 2%. Various patient‐level (affordability, willingness to take multidrug regimens), clinician‐level (comfort with newer agents, knowledge gaps, treatment inertia), and health system‐level (local treatment availability, access to healthcare) issues may contribute to observed gaps in evidence‐based therapies 19,21,22,24 . Multilevel quality improvement initiatives are needed to promote equitable and widespread care practices to optimize GDMT.…”
Section: Discussionmentioning
confidence: 99%
“…This group of patients has been frequently underrepresented in previous HF trials, which might have discouraged clinicians from generalizing GDMT for HF. 8 Despite the common practice of implementing neurohumoral blockade therapy for HFrEF, there is a lack of definite recommendations in guidelines with supporting evidence. The post hoc analysis of the PARADIGM‐HF study confirmed consistent additional benefits of ARNI over enalapril across different aetiologies of HF, including ischaemic (60.0%), hypertensive (9.5%), idiopathic HF (11.5%), and others (19.0%).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the lack of solid clinical evidence in this group of patients, 4 , 8 angiotensin‐converting enzyme inhibitors (ACEI) and angiotensin II receptor blockers (ARB) are recommended if patients present with heart failure with reduced ejection fraction (HFrEF) before or after valve interventions. 4 , 9 In recent years, the superiority of the angiotensin receptor‐neprilysin inhibitor (ARNI) sacubitril/valsartan over ACEI or ARB in HFrEF has been recognized, 4 , 10 , 11 but it is uncertain whether this also applies to residual LV remodelling after AR or MR surgery.…”
Section: Introductionmentioning
confidence: 99%
“…As an alternative, the much-supported option of guideline-directed medical therapy for HF should, in theory, be easier to apply in primary care given the availability of subsidised and approved therapies. [ 17 ] However, as typically occurs in the primary care HF population, this strategy is not so easily applied when a GP is faced with an ‘atypical’ patient who would have been excluded from a clinical trial because of their advanced age, type of HF (e.g. predominantly right sided) and multimorbidity.…”
Section: Paucity Of Primary Care Trialsmentioning
confidence: 99%
“…Thus, as with any new agent or clinical indication in HF, there is an inherent expectation on primary care to consider and manage complicated issues around the benefits versus risks of continuing agents, such as the SGLT2 inhibitors, while attempting to interpret trial evidence derived from typically younger, less complicated patients. [ 17 ]…”
Section: Treating Hfpefmentioning
confidence: 99%